Class II Skeletal Malocclusion Correction with Herbst Appliance - Yezdani, A. Arif; Sreenivasan, Prashanth; Padmavati, R.; Kumar, S. Kishore; Padmavathy, Kesavaram (Highlights on Medicine and Medical Research Vol. 2, 2021)
Introduction: Class II skeletal jaw discrepancy since time immemorial has posed an enigma to the practising orthodontists. This case report describes the treatment of a skeletal Class II malocclusion with an orthognathic maxilla and retrognathic mandible with severely proclined maxillary incisors, imbricated mandibular incisors, deep bite, convex profile and horizontal mandibular growth pattern treated with the Herbst appliance. Methods: Visual treatment objective was initially done to confirm the effectiveness of the use of a functional appliance. Treatment involved the use of a fixed functional appliance namely, Herbst appliance to advance the mandible forwards. The case was assessed at T1 and T2 of the initial orthopedic phase of treatment. Results: At T2, the retrognathism of the mandible was adequately addressed and the facial convexity reduced dramatically. The molars attained a Class I relation and the facial soft tissue profile improved drastically with elimination of lower lip trap. Conclusion: Functional retrusion of the mandible can be effectively treated in the pubertal period of growth spurt with the judicious use of a fixed functional bite jumping appliance such as the Herbst.